2007
DOI: 10.1016/j.bbrc.2007.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Expression and initial characterization of human ALDH3B1

Abstract: Aldehyde dehydrogenases (ALDHs) are critical enzymes in the metabolism of endogenous and exogenous aldehydes. The human genome contains nineteen putatively functional ALDH genes; ALDH3B1 belongs to the ALDH3 family. While recent studies have linked the ALDH3B1 locus to schizophrenia, nothing was known, until now, about the properties and significance of the ALDH3B1 protein. The aim of this study was to characterize the ALDH3B1 protein. Human ALDH3B1 was baculovirus-expressed and found to be catalytically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Recent data suggest that this enzyme reacts with medium-and long-chain aliphatic aldehydes, potential products of fatty acids released by the droplet, and thereby protects the cell from oxidative stress ( 66 ).…”
Section: Two Other Enzymes Of Lipid Metabolism Of the Droplet Proteommentioning
confidence: 99%
“…Recent data suggest that this enzyme reacts with medium-and long-chain aliphatic aldehydes, potential products of fatty acids released by the droplet, and thereby protects the cell from oxidative stress ( 66 ).…”
Section: Two Other Enzymes Of Lipid Metabolism Of the Droplet Proteommentioning
confidence: 99%
“…ALDH3B1 is also expressed ubiquitously, and its protein levels are high in the kidney, liver, and ovary [15,16]. Similar to ALDH3A2, human ALDH3B1 exhibits activity toward medium-chain to long-chain aldehydes; in contrast to ALDH3A2, its subcellular localization is in the plasma membrane [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stable expression of ALDH3B1 protects cultured cells from cytotoxicity induced by LPO-derived aldehydes. As such, we postulate that ALDH3B1, similar to other members of the ALDH3 family (Pappa et al 2003), plays an important physiological role against cellular oxidative stress by detoxifying aldehydes derived from oxidative processes, such as ethanol metabolism and LPO (Marchitti et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Using Western blot analyses, we previously have shown that an ALDH3B1 85% similar to the human enzyme is expressed in various mouse tissues, including kidney, liver, lung, and regions of the brain (Marchitti et al 2007b). However, IHC permits cellular (and subcellular) protein expression to be identified; therefore, it can be used to further elucidate the potential physiological roles and significance of proteins in human tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation